Effect of Heat Stress on Bucks Adaptability and Semen Characteristics - Rahman, A; Hossain, MM; Khan, M; Kamal, MT; Hashem, MA (Journal of Environmental Science and Natural Resources, 2016)
The experiment was conducted to investigate the effect of heat stress on adaptability and semen quality of buck. Almost similar 10 Black Bengal bucks were selected for the study at Artificial Insemination Centre, Bangladesh Agricultural University, Bangladesh. Prerequisite biological data were collected from each animal before keeping them sun heat and after 1 hour sun exposure. Different semen characteristics of each animal were measured. Temperature humidity index (THI) was 19.95 in the morning which indicate all the animals were in absence of heat stress and THI was 25.54 in the noon which indicate all the animals were in severe heat stress at noon. Buck 1 and buck 5 were more heat resistant (p<0.01), because their thermolysis capacity (TC) values were less than the others. There were no differences in tunica dartos index and semen characteristics among different bucks (p>0.05). Positive correlation between sperm motility and testis length (p<0.05), and negative correlation between sperm concentration and scrotal skin temperature (p<0.05) were found. From the study it can be concluded that all the bucks were in severe heat stress at noon time and TC can be used as an indicator for selection of buck for heat tolerance. J. Environ. Sci. & Natural Resources, 9(1): 151-156 2016